2003
DOI: 10.1051/vetres:2003028
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring udder health and milk quality using somatic cell counts

Abstract: -In this article the use of somatic cell counts for monitoring udder health and milk quality is discussed. Somatic cell count dynamics at quarter, cow, herd and population level are discussed and illustrated with examples. Quarter and cow somatic cell counts directly represent the inflammatory status of the mammary gland. Herd and population somatic cell count are related to the inflammatory process in individual cows but much more reflect the udder health status of the herd and the quality of the raw milk in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
401
1
50

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(507 citation statements)
references
References 44 publications
17
401
1
50
Order By: Relevance
“…Thus, composite measurements of SCC for monitoring IMI incidence may be unreliable. Schukken et al (2003) have reported that the most accurate relationship between IMI and SCC exists at the quarter level, which also supporting our findings. The predictive values of composite SCCs are dependent on the numbers of infected quarters and of pathogens involved in IMIs, as milk from infected quarters is diluted with normal milk from uninfected quarters (Reyher & Dohoo 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, composite measurements of SCC for monitoring IMI incidence may be unreliable. Schukken et al (2003) have reported that the most accurate relationship between IMI and SCC exists at the quarter level, which also supporting our findings. The predictive values of composite SCCs are dependent on the numbers of infected quarters and of pathogens involved in IMIs, as milk from infected quarters is diluted with normal milk from uninfected quarters (Reyher & Dohoo 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the milk somatic cell count (SCC) has been extensively used as an indicator of IMI; the SCC is included as a component of the definition of mastitis, as the milk SCC markedly increases during infection (Pyörälä 2003, Schukken et al 2003, Della Libera et al 2011, Dufour & Dohoo 2013. Altogether, we hypothesized that isolation of the infection agent affect the SCC thresholds used to detect infected quarters or cows, as microbiological culture has long been considered the gold standard test compared with other mastitis diagnostic tests (Pyörälä 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic accuracy of the milk electrical resistance (MER) and California milk cell test (CMCT) were estimated relative to two classifications of mastitis: a quarter-level somatic cell count (SCC) of greater than 200,000/ml (Schukken et al, 2003) and the successful isolation of a pathogenic bacterial organism. Only cows sampled during the first herd visit were used to evaluate diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…As glândulas mamárias foram consideradas infectadas quando foi isolado pelo menos um agente causador de mastite no exame bacteriológico. Os quartos mamários negativos no exame bacteriológico foram divididas em dois grupos experimentais, o primeiro com baixa celularidade (<200.000 células/mL), quartos mamários que foram considerados como sadios conforme previamente estabelecido por Schukken et al (2003), e o segundo grupo foi formado por quartos mamários negativos no exame bacteriológico, mas com alta CCS (>200.000 células/mL).…”
Section: Methodsunclassified